Effect of broiler chicken age on ileal digestibility of corn germ meal - doi: 10.4025/actascianimsci.v34i2.11812 - Lima, Michele Bernardino; Rabello, Carlos Bôa-Viagem; Silva, Edney Pereira da; Lima, Rodrigo Barbosa; Arruda, Emmanuele Maria Florêncio de; Albino, Luiz Fernando Teixeira (Acta Scientiarum. Animal Sciences, 2011)
The objective of this research study was to evaluate the effect of age on the apparent ileal digestibility coefficient of nutrients, gross energy and digestible energy of corn germ meal for broilers. Four digestibility trials were conducted using 280 broilers (Cobb 500) distributed in a completely randomized design with two treatments and five replications, repeated at four ages (10, 20, 30 and 40 days). The number of birds used in the tests was 10, 8, 6 and 4 birds per experimental unit at the different ages. The results were analyzed considering as dependent variable the apparent ileal digestibility of dry matter, crude protein, ether extract and gross energy, digestible dry matter, digestible crude protein, lipid and digestible energy; and ages (10, 20, 30 and 40 days) as the independent variable. The results for the variables showed that bird age exerted influence only in the ileal digestibility of dry matter and gross energy. The digestible energy of corn germ meal increased by about 13 kcal kg-1 day-1 up to the evaluated age (40 days)